Clinical outcomes of patients with multiple sclerosis treated with ocrelizumab in a US community MS center: an observational study. Issue 2 (7th July 2021) - Smoot, Kyle; Chen, Chiayi; Stuchiner, Tamela; Lucas, Lindsay; Grote, Lois; Cohan, Stanley
Abstract : Background: To monitor long-term outcomes of ocrelizumab treatment. Objective: To evaluate safety and treatment outcomes of ocrelizumab in a community-based multiple sclerosis (MS) population. Methods: Adult patients with MS prescribed ocrelizumab were eligible. Chart reviews were conducted at the start of ocrelizumab treatment and every 6 months thereafter. Results: Of the 355 patients enrolled, 71.9% were female; mean (SD) age was 51.8 (12.5) years; 78.3% had relapsing MS (RMS). Median baseline Expanded Disability Status Scale (EDSS) (IQR) was 3.0 (2.0–4.0) for RMS, 6.5 (6.0–7.5) for secondary progressive MS, and 6.5 (6.0–7.0) for primary progressive MS. Respiratory infections occurred in 40.1% and urinary tract infections in 33.1% of patients. There was no difference in the percentage of infections among patients <55 (68.5%, n=122), and those ≥55 of age (67.5%, n=104) (p=0.94). Twenty-five hospitalisations were due to infections; 69.2% of these patients were ≥55 with a mean EDSS of 5.7 (±1.86). Four patients have died. Serum IgM and IgG levels did not predict infection risk. Annualised relapse rate was 0.34 for the patients with RMS in the preceding 2 years and 0.09 in patients who received ≥2 ocrelizumab 600 mg courses. The first on-treatment MRI was stable in 262 (90.0%) patients, 6.9% had new T2 lesions, 2.7% had enlarging T2 lesions and 1.4% had gadolinium-enhancing lesions. Median EDSS at 12 months was unchanged. Conclusion: Ocrelizumab effectively controlled relapse risk and disability worsening. Although only 12.1% of patients have discontinued ocrelizumab, infections resulting in hospitalisation are a concern, especially in older and disabled patients.